2010
DOI: 10.1002/pbc.22619
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity of pandemic H1N1 influenza in children with cancer

Abstract: H1N1 infection in children with cancer was not reported as the cause of death in any case but resulted in reduced intensity of anti-cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
2
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 3 publications
4
29
2
4
Order By: Relevance
“…3 Two small studies of children with malignancies infected with the A/H1N1 pandemic strain also suggest relatively mild disease. 18,19 Lymphopenia has been identified as a risk factor for LRT disease, both for influenza and for infections with other respiratory viruses. 5 Although we found that neutropenia was a significant risk factor for death, this was not the case for pneumonia or for mechanical ventilation.…”
Section: Resultsmentioning
confidence: 99%
“…3 Two small studies of children with malignancies infected with the A/H1N1 pandemic strain also suggest relatively mild disease. 18,19 Lymphopenia has been identified as a risk factor for LRT disease, both for influenza and for infections with other respiratory viruses. 5 Although we found that neutropenia was a significant risk factor for death, this was not the case for pneumonia or for mechanical ventilation.…”
Section: Resultsmentioning
confidence: 99%
“…Pathogens as Pseudomonas spp., Enterobacter spp., Streptococcus spp. and coagulase-negative staphylococci [6,8] have been described. Secondary bacterial infections may also occur as clinical infections, such as pneumonia or otitis media [10].…”
Section: Complicationsmentioning
confidence: 99%
“…In one population of children with 2009 pandemic influenza infection, 55% of the children experienced treatment delays averaging 3 weeks; the longest delay in this group was 43 days. Others have also reported average treatment interruptions of 3 weeks or more [6,8]. The impact of treatment interruptions due to influenza specifically is unknown; however, emerging evidence suggests that relapse rates are higher among children with acute…”
Section: Impact On Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…И уже не остается сомнений, что это совсем не «безобидное» заболевание. В результате сдвига микробио-ценоза влагалищной среды женщины становятся более уязвимыми перед агрессией различных микроорганиз-мов, таких как дрожжеподобные грибы рода Candida [5].…”
unclassified